Slope Reinforcement Due to Landslide in Cipakancilan River, Sukaresmi Village, Bogor City - Lutfi, Muhamad; Chayati, Nurul; Rulhendri, Rulhendri; Syaiful, Syaiful; Sunandar, Nandar; Insan, Muhammad Khaerul (Universitas Ibn Khaldun Bogor, 2025)
In October 2022, there was a landslide in Tanah Sareal Subdistrict at Cipakancilan River, Sukaresmi Village, Bogor City. The location of the landslide occurred on the edge of the road adjacent to the Cipakancilan river, the road is an access road that connects the Regency area and the Bogor City area. The length of the landslide that occurred was 30 meters and 11.5 meters high from the Cipakancilan river water level. The construction of a retaining wall (DPT) is the right solution to maintain slope stability, namely rolling stability, shear stability and soil bearing capacity stability to restore stable slope conditions to hold the road body which can be reused as an access road for residents. This research started with an initial stage in the form of a field survey, then continued with a geotechnical investigation to determine the characteristics of the soil that experienced landslides. Based on the results of the research, it was found that the design of retaining walls of gravity type and cantilever type was analyzed using the Coulomb method for calculating lateral soil pressure and Mayerhof for calculating the stability of soil bearing capacity. For construction costs from the calculation of the cost budget plan, the results obtained for the gravity type retaining wall amounted to Rp. 1,229,923,600 (one billion two hundred twenty nine million nine hundred twenty three thousand rupiah), while the cantilever type retaining wall amounted to Rp. 1,620,913,000. 1,620,913,000 (one billion six hundred twenty million nine hundred thirteen thousand rupiah), the time of the planned implementation of gravity retaining wall work for 2.5 months or 75 calendar days, the time of the planned implementation of cantilever retaining wall work for 3 months or 90 calendar days.